Peculiarities of functional connectivity - including cross-modal patterns - in professional karate athletes: Correlations with cognitive and motor performances - Berti, B.; Momi, D.; Sprugnoli, G.; Neri, F.; Bonifazi, M.; Rossi, A.; Muscettola, M. M.; Benocci, R.; Santarnecchi, E.; Rossi, S. (Neural Plasticity, 2019)
Professional karate is a sport activity requiring both physical and psychological skills that have been associated with a better "global neural efficacy." By means of resting state functional magnetic resonance imaging (rs-fMRI), we investigated the neural correlates of cognitive and kinematic abilities in a group of 14 professional karateka and 14 heathy matched controls. All subjects underwent an extensive cognitive test battery for the identification of individual multidimensional cognitive profile and rs-fMRI scans investigating functional connectivity (FC). Moreover, kinematic performances in athletes were quantified by the Ergo-Mak, an integrated system developed for measuring motor reactivity, strength, and power of athletic gestures. Karateka performed significantly better than controls in the visual search task, an ability linked with increased positive correlations in FC between the right superior parietal lobe and bilateral occipital poles. Kinematic performances of athletic feats were sustained by increased positive correlations between subcortical (cerebellum and left thalamus) and cortical (inferior frontal cortex, superior parietal cortex, superior temporal cortex) regions. An unexpected FC increase between auditory and motor-related areas emerged in karateka, possibly reflecting a cross-modal coupling due to the continuous exposure to either internal or external auditory cues, positing this sensory channel as a possible target for novel training strategies. Results represent a further step in defining brain correlates of "neural efficiency" in these athletes, whose brain can be considered a model of continuous plastic train-related adaptation.